Mortalidad por cáncer bucal en la provincia de Córdoba, República Argentina (período 1975-2000). Estudio comparativo con otras poblaciones - Morelatto, R. (2014)
The activity of Nitric Oxide Synthase 2 (NOS2) was found in oral squamous cell carcinomas (OSCC) but not in normal mucosa. Molecular changes associated to early carcinogenesis have been found in mucosa near carcinomas, which is considered a model to study field cancerization. The aim of the present study is to analyze NOS2 expression at the histologically normal margins of OSCC. Study Design: Eleven biopsy specimens of OSCC containing histologically normal margins (HNM) were analyzed. Ten biopsies of normal oral mucosa were used as controls. The activity of NOS2 was determined by immunohistochemistry. Salivary nitrate and nitrite as well as tobacco and alcohol consumption were also analyzed. The Chi-squared test was applied. Results: Six out of the eleven HNM from carcinoma samples showed positive NOS2 activity whereas all the control group samples yielded negative (p=0.005). No statistically significant association between enzyme expression and tobacco and/or alcohol consumption and salivary nitrate and nitrite was found. Conclusions: NOS2 expression would be an additional evidence of alterations that may occur in a state of field cancerization before the appearance of potentially malignant morphological changes.